Competence and career success among psychologists: a qualitative approach - Mendonça, M.; Magalhães, E.; Calheiros, M. M. (32nd International Congress of Psychology: ICP2020+, 2021)
Psychologists have a high responsibility role to play in different contexts, such as clinical, organizational, educational, sports, community, and research. Therefore, it is essential to identify, evaluate, and disseminate methods to ensure their competence. Competence is a broad concept that means the ability to perform at an acceptable level, and it involves multiple dimensions interrelated. Knowledge about psychologists' competence has increased in the last decade, but it is still not clear how professionals develop them. Moreover, psychologists support and guide others towards positive change and success, but we lack information on their career success. Career success usually combines two dimensions: (1) objective (including salary and promotions), and (2) subjective (e.g., satisfaction, recognition). Nevertheless, research on success among psychologists usually measures intervention outcomes only. It means that psychologists' success has been evaluated by an external view based on performance, not considering their perception of the topic. Our study aims to understand how psychologists perceive (1) professional competence, and (2) career success, identifying their perceptions about the mechanisms behind both concepts. The absence of studies on social and organizational predictors of competence and career success from the psychologists' perspective justifies the use of a qualitative and exploratory methodology. We performed 12 focus groups with psychologists (N=67) with different backgrounds and years of experience. Data was collected through a semi-structured script and it was analyzed using thematic analysis. Results will be presented and discussed according to the literature and theory on this topic.